2017
DOI: 10.1503/cmaj.160636
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that supports policies to delay cervical screening until after age 25 years

Abstract: New guidelines for cervical screening from Alberta 1 and British Columbia 2 recommend increasing the starting age from 21 to 25 years. These guidelines follow the recommendations published by the Canadian Task Force on Preventative Health Care in 2013, 3 and are similar to many other highincome countries. Cervical cancer mostly has a long natural history and, consequently, is uncommon in women under age 25 years. Cervical screening among this age group has minimal impact on rates of carcinoma but does lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, targeting women aged 25 years and above has both screening benefits and reduced harms due to overtreatment. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, targeting women aged 25 years and above has both screening benefits and reduced harms due to overtreatment. 11 …”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we included studies with women who are 25 years and older because HPV screening among women less than 25 years leads to overdiagnosis and overtreatment. However, targeting women aged 25 years and above has both screening benefits and reduced harms due to overtreatment 11…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the majority of dysplastic cervical lesions, which are common in this age group have a tendency to regress spontaneously [21]. Therefore, covering this age group with screening may lead to overdiagnosis and subsequently -overtreatment of precancerous lesions [24]. However, Nygård et al [20] showed that women who perform Pap smear frequently have a tendency to follow this pattern, whereas those who do it seldomly or never, have no tendency to participate in screening in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The trial personnel often performed cervical screening together with colposcopy every 6 months, and the included participants were often women aged 15-26. In clinical practice, cervical screening is usually performed every 3 to 5 years and recommended after age 25 [44], as most CIN2 + lesions in women under age 30 regress spontaneously, which may justify active surveillance rather than immediate intervention [45].…”
Section: Limitations Of Benefit Assessmentmentioning
confidence: 99%